1996
DOI: 10.1099/00222615-44-5-325
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of strains of Salmonella serotype Livingstone by multiple typing

Abstract: Isolates of Salmonella serotype Livingstone (6,7:d: 1,w) from man, water and various animals and animal products in Canada, England, France, Israel and Scotland were examined for ribotype, biotype and plasmid profde. Analysis by these methods indicated that an epidemic strain of Livingstone of ribotype lhiotype 8/plasmid-type 6 was responsible for the major upsurge of Livingstone infection that occurred in man in Tayside (Scotland) between 1989 and 1991; that type was also isolated from spring water, animal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…However, the results of both approaches (PFGE and ribotyping) for the epidemiological evaluation of the isolates involved in this outbreak suggested that it was caused by the same clone. Salmonella serotype Livingstone has been isolated previously from poultry in other countries: Canada (11), Scotland (11,35), Japan (28), England (11), and France (13). Between 1980 and 1985 in Scotland, poultry and poultry products were an important vehicle for human salmonellosis, since poultry meat accounts for Ͼ50% of all human Salmonella outbreaks where a food vehicle has been identified (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of both approaches (PFGE and ribotyping) for the epidemiological evaluation of the isolates involved in this outbreak suggested that it was caused by the same clone. Salmonella serotype Livingstone has been isolated previously from poultry in other countries: Canada (11), Scotland (11,35), Japan (28), England (11), and France (13). Between 1980 and 1985 in Scotland, poultry and poultry products were an important vehicle for human salmonellosis, since poultry meat accounts for Ͼ50% of all human Salmonella outbreaks where a food vehicle has been identified (35).…”
Section: Discussionmentioning
confidence: 99%
“…The present study, in agreement with previous experiments (11), found that the vast majority of serovar Enteritidis strains carry just the serospecific virulence plasmid. Extrachromosomal DNA is regarded as an unstable genetic marker (2,5). Also, it is recognized that strains with the same chromosomal features may show different plasmid restriction patterns (28) and that the same plasmid profile may be present in strains which are different at a chromosomal level (24).…”
Section: Figmentioning
confidence: 99%
“…It also provided a good level of discrimination for serotype Senftenberg. Previous studies have found plasmid profiling to be of use in intraserotype differentiation (6,20,24), although many of these were performed prior to the widespread implementation of the more advanced methods of PFGE and ribotyping. Few recently published articles involve the use of plasmid profiling as a stand-alone procedure.…”
Section: Fig 1 Dendrogram Generated By the Gel Compar II Software Smentioning
confidence: 99%
“…This is a limitation which must be recognized in epidemiological research and has brought into question what can be regarded as a suitable plasmid profile for analysis. Some studies (6) regard the presence of a single, identical plasmid as sufficient proof that isolates are identical and therefore epidemiologically related. Other studies (15) suggest that numerous plasmids must be present and regard the presence of a single plasmid insufficient as representative of a clone.…”
Section: Fig 1 Dendrogram Generated By the Gel Compar II Software Smentioning
confidence: 99%
See 1 more Smart Citation